2007
DOI: 10.1111/j.1574-0862.2007.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers from high‐value agriculture for exports on land use in developing countries: evidence from Madagascar

Abstract: High-value agriculture for exports is increasingly important in developing countries. In a case study of contract farming for exports of vegetables from Madagascar, strong spillover effects of these trade opportunities on land use are found to exist. Using a matched plot sampling design, the productivity of rice-the main domestically consumed staple-is shown to be two-thirds higher on fields that were contracted during the off-season for the production of vegetables. This increase in yields is linked to an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 18 publications
(25 reference statements)
2
39
0
Order By: Relevance
“…Using micro-survey evidence from Ethiopia and a matched plot pair design through which we control for the effect of plot and farmer characteristics, we find that food crop productivity improved on plots intercropped with biofuel feedstock (castor) due to enhanced access to inputs and technical assistance which were provided as part of the feedstock production contracts. Our estimates are in line with studies which have identified similar spillover effects of cash crop production on food crop productivity (Maertens, 2009;Minten et al, 2007;Barrett et al, 2012).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using micro-survey evidence from Ethiopia and a matched plot pair design through which we control for the effect of plot and farmer characteristics, we find that food crop productivity improved on plots intercropped with biofuel feedstock (castor) due to enhanced access to inputs and technical assistance which were provided as part of the feedstock production contracts. Our estimates are in line with studies which have identified similar spillover effects of cash crop production on food crop productivity (Maertens, 2009;Minten et al, 2007;Barrett et al, 2012).…”
Section: Introductionsupporting
confidence: 90%
“…This is an issue which has received little attention in the biofuel literature but has been widely studied in the literature on cash crops and export agriculture (e.g. Minten et al, 2007). In the rest of this paper, we analyze these spillover effects from biofuel crops and we study how they affect food production, and thus food security, at the household level.…”
Section: Castor Production and Food Security In Ethiopiamentioning
confidence: 99%
“…While a few studies have analyzed productivity effects of supermarket or export channel participation (e.g., Hernández, Reardon, and Berdegué 2007;Minten, Randrianarison, and Swinnen 2007;Neven et al 2009), we are not aware of any research that has taken a disaggregated view on different potential sources of productivity growth, such as changes in technology, technical efficiency, or scale efficiency. As productivity growth in smallholder agriculture can be an important avenue for poverty reduction (World Bank 2007), a better understanding of the sources and mechanisms for realizing the same is important from a development policy perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have analyzed the determinants of farmer participation in modern supply chains, including supermarket and export channels, and impacts on farm and household incomes (Hernández, Reardon, and Berdegué 2007;Maertens and Swinnen 2009;Rao and Qaim 2011). There are also studies that have looked into effects for more traditional markets and spillovers on land use and rural employment (Minten, Randrianarison, and Swinnen 2007;Schipmann and Qaim 2010;Maertens, Colen, and Swinnen 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The immense political, climatic, technological and economic challenges faced by peasants in these countries are well-documented (e.g. O'Brien and Leichenko 2000;Misselhorn 2005;Minten et al 2007). Conventional farming practices are afflicted by free market pressure to produce more food for less income, resulting in poverty, the destruction of the environment, neglecting animal welfare and human social justice.…”
Section: Introductionmentioning
confidence: 99%